2015
DOI: 10.1111/nph.13685
|View full text |Cite
|
Sign up to set email alerts
|

Multiple paths to similar germination behavior in Arabidopsis thaliana

Abstract: SummaryGermination timing influences plant fitness, and its sensitivity to temperature may cause it to change as climate shifts. These changes are likely to be complex because temperatures that occur during seed maturation and temperatures that occur post-dispersal interact to define germination timing.We used the model organism Arabidopsis thaliana to determine how flowering time (which defines seed-maturation temperature) and post-dispersal temperature influence germination and the expression of genetic vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
104
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(111 citation statements)
references
References 72 publications
7
104
0
Order By: Relevance
“…Genome-wide association and genetic linkage mapping analyses have implicated the DOG1 locus in the regulation of flowering phenotypes (22,23), but these results were attributed to the possibility of being caused by closely linked genes, as DOG1 was assumed to be active only in seeds. However, our results demonstrate that DOG1 itself can have effects on seed dormancy and flowering, suggesting a more direct mechanism for the evolutionary coadaptation of lifecycle transitions to match seasonal environmental conditions (16,44,49,50). In addition, previous studies have shown that genes related to flowering are expressed in association with seed development and germination.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Genome-wide association and genetic linkage mapping analyses have implicated the DOG1 locus in the regulation of flowering phenotypes (22,23), but these results were attributed to the possibility of being caused by closely linked genes, as DOG1 was assumed to be active only in seeds. However, our results demonstrate that DOG1 itself can have effects on seed dormancy and flowering, suggesting a more direct mechanism for the evolutionary coadaptation of lifecycle transitions to match seasonal environmental conditions (16,44,49,50). In addition, previous studies have shown that genes related to flowering are expressed in association with seed development and germination.…”
Section: Discussionmentioning
confidence: 51%
“…A dual role in sensing environmental signals (e.g., temperature) and coordinating developmentalphase transitions in the plant life cycle would explain the repeated identification of DOG1 as a significant locus in ecological genetics studies of flowering phenotypes (22,23,48). It would also make evolutionary sense, as seed dormancy and germination timing influence the environment in which subsequent flowering and reproduction occur, and vice versa (16,44,50). An integrated mechanism for coordinating these two major life cycle transitions having significant impacts on fitness and survival would be subject to coselection to optimize (or bet-hedge) both (9,11,43,49,50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we used the Columbia (Col) accession to compare germination responses to vegetative canopies in the two standard lab strains of A. thaliana (Ler and Col) that are known to differ in germination behaviour. Col is less dormant than Ler under most conditions (Chiang et al, 2009;Burghardt et al, 2016).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 97%
“…We used three imbibition light treatments -white light (12 h photoperiod), green filter (12 h photoperiod, 'canopy' hereafter) and dark -and two imbibition temperatures -10 and 22 C. Comparisons between the white light and dark treatments test whether light is required for germination, while comparisons between the white light and canopy treatments test for germination responses to a canopy during imbibition. Comparisons between temperatures (10 and 22 C) test whether the effects of genotype, maturation light and imbibition light are more likely to occur when seeds experience temperatures that promote germination (10 C) as opposed to temperatures that are less conducive to germination (Auge et al, 2015;Burghardt et al, 2016).…”
Section: Germination Assaysmentioning
confidence: 99%